Expression of Components of the Renin-Angiotensin System by the Putative Stem Cell Population Within WHO Grade I Meningioma - Shivapathasundram, Ganeshwaran; Wickremesekera, Agadha C.; Brasch, Helen D.; van Schaijik, Bede; Marsh, Reginald W.; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2019)
Aim: We have recently demonstrated a stem cell population within WHO grade 1 meningioma (MG) that expressed embryonic stem cell (ESC) markers OCT4, NANOG, SOX2, KLF4 and c-MYC localized to the endothelial and pericyte layers of the microvessels. There is increasing recognition that the renin-angiotensin system (RAS) plays a critical role in stem cell biology and tumorigenesis. This study investigated the expression of components of the RAS: pro-renin receptor (PRR), angiotensin converting enzyme (ACE), angiotensin II receptor 1 (ATIIR1) and angiotensin II receptor 2 (ATIIR2) on the putative stem cell population on the microvessels of WHO grade 1 MG. Methods: 3,3-Diaminobenzidine (DAB) immunohistochemical (IHC) staining was performed on WHO grade 1 MG tissue samples from 11 patients for PRR, ACE, ATIIR1 and ATIIR2. Two of the MG samples subjected to DAB IHC staining underwent immunofluorescence (IF) IHC staining to investigate co-expression of each of these components of the RAS in using combinations of CD34 and ESC marker SOX2 or OCT4. NanoString mRNA expression analysis and Western blotting (WB), were performed on six snap-frozen MG tissue samples to confirm transcriptional activation and protein expression of these proteins, respectively. Results: DAB IHC staining demonstrated the expression of PRR, ACE, ATIIR1 and ATIIR2 within all 11 MG tissue samples. WB and NanoString mRNA analyses, confirmed protein and mRNA expression of these proteins, respectively. IF IHC staining showed PRR, ATIIR1 and ATIIR2 were localized to the OCT4+ and SOX2+ endothelium and pericyte layer of MG while ACE was localized to the OCT4+ endothelium of the microvesels. Conclusion: The novel finding of the expression of PRR, ACE, ATIIR1 and ATIIR2 on the putative stem cell population on the microvessels of WHO grade 1 MG. suggests that these stem cells may be a potential therapeutic target by manipulation of the RAS.